DEVELOPING ACTIVITY, MOTIVATION AND COGNITIVE DEVELOPMENT THROUGH MAMA PAPA MODEL IN EARLYCHILDHOOD - Linda Rahmaniah; Noorhapizah Noorhapizah (E-CHIEF Journal, 2022)
The problem of this research is the low activity, motivation and cognitive of children in recognizing number symbol. The purpose of the study was to describe activity, motivation and cognitive development through the Make a Match model, Picture and Picture model, and the Flannel Board media. The type of research is classroom action with four meetings. The research subject was group A with a total of 5 children, there are 3 girls and 2 boys. The result showed that the teacher's activity at the fourth meeting with a very good category with a score of 26. In the first meeting children's activity with a percentage of 40% in the category of a small number of active children until the fourth meeting with a percentage of 100% in the category of all active children. The motivation of children in the first meeting with a percentage of 40% in the less motivated category to the fourth meeting with a percentage of 100% in the highly motivated category. The result of cognitive development from the first meeting with a percentage of 20% to the fourth meeting with a percentage of 100% or 5 children who successfully developed in the BSH category and were very active. It is suggested that the MAMA PAPA model can increase children's activity, motivation and cognitive recognizing of number symbol